2014
DOI: 10.5376/jmr.2014.04.0012
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical extractions from the leaves of <i>Ravenala madagascariensis</i> from Sundarban area and its effect on southern house mosquito (<i>Culex quienquefasciatus</i> Say 1823) larvae

Abstract: Vector control is a major issue mainly in this time when resistance to chemical insecticides leads to a greater problem. For an alternative measure novel botanical sources can be used as a good insecticide with less toxic hazards to the environment and public health. The present study estimated larvicidal activities of the crude and solvent extracts of Ravenala madagasariensis against the filarial vector Culex quinquefasciatus under laboratory conditions. Crude extracts of R. madagasariensis mature leaves were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Owoeye et al (2016), Hamza et al (2014) further reported that A. gambiae and A. arabiensis are the main species that transmit malaria. Bhattacharya et al (2014b), Ndiok et al (2016) also reported that Culex quinquefasciatus transmits lymphatic filariasis. Adebajo et al (2014) reported that Aedes aegypti transmits chikungunya, yellow and dengue fevers.…”
mentioning
confidence: 99%
“…Owoeye et al (2016), Hamza et al (2014) further reported that A. gambiae and A. arabiensis are the main species that transmit malaria. Bhattacharya et al (2014b), Ndiok et al (2016) also reported that Culex quinquefasciatus transmits lymphatic filariasis. Adebajo et al (2014) reported that Aedes aegypti transmits chikungunya, yellow and dengue fevers.…”
mentioning
confidence: 99%
“…TLC of chloroform: methanol extract indicated the existence of steroidal compounds and bioassay reveals a significant death rate in that fraction (p<0.05). Chloroform: methanol extract from some other plants is also reported to exhibit mosquito larvicidal potential [35,44,45] and comparisons show that the LC 50 value of the chloroform: methanol extract fraction of V. spinosa leaves against Cx. quinquefasciatus larvae are quite acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Larval control is easier than control of adults due to their low mobility and confinement to water bodies. (Bhattacharya et al, 2014b) and Solanum nigrum berry (Rawanietal, 2013) showed potent larvicidal property against Cx. quinquefasciatus.…”
Section: Discussionmentioning
confidence: 99%